Analysis of polarimetric bistatic sea clutter using the NetRAD radar system. Issue 8 (1st October 2016) - Fioranelli, Francesco; Ritchie, Matthew; Griffiths, Hugh; Sandenbergh, Stephan; Inggs, Michael
Abstract : This study presents a comparative analysis of amplitude and Doppler spectra statistics from monostatic and bistatic sea clutter data at S‐band. These data cover a range of bistatic angles from 60° to 120° and include simultaneous monostatic and co‐polarised and cross‐polarised bistatic recordings, providing direct comparison of their statistical properties. The time series of amplitude data are fitted to the compound K and K + noise distribution in the range domain and in the Doppler domain, and the variation of the shape parameter is presented for monostatic and co‐polarised and cross‐polarised bistatic data as an indication of the spikiness of the clutter. From the analysis of this parameter, it is shown that cross‐polarised bistatic data tend to be less spiky in the range and Doppler domain than the simultaneous co‐polarised bistatic data, and than the simultaneous monostatic data, which could be advantageous in terms of radar detection performance, especially for low‐visibility maritime targets.